A high-strength lead-bismuth corrosion-resistant additively manufactured metastable stainless steel alloy material and its preparation method

By optimizing the composition and additive manufacturing process of metastable stainless steel alloys, high-strength additive manufacturing metastable stainless steel alloy materials were prepared, which solved the problem of corrosion of materials in the fourth-generation lead-bismuth fast stack in liquid lead-bismuth environment, and achieved high strength and good corrosion resistance.

CN118345317BActive Publication Date: 2025-03-07SHANGHAI JIAOTONG UNIV
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202410467922.7
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-04-18
Publication Date
2025-03-07
Estimated Expiration
2044-04-18

AI Technical Summary

Technical Problem

In the fourth generation lead-bismuth fast reactor, structural materials are easily corroded by liquid lead-bismuth under high temperature, high pressure and strong neutron radiation environments, resulting in deterioration of material performance and affecting the safety and reliability of nuclear reactors.

Method used

By optimizing the composition and additive manufacturing process of metastable stainless steel alloys, high-strength additive manufacturing metastable stainless steel alloy materials are prepared. The maximum particle size of the alloy powder of this material is less than 150μm, with high spherical shape and low hollow spherical rate. Laser printing is performed using interlayer rotation and strip scanning strategy to form a material with good mechanical properties and resistance to lead-bismuth corrosion.

Benefits of technology

It realizes high strength and good corrosion resistance of materials in liquid lead-bismuth environments, effectively solves the problem of corrosion in traditional materials in this environment, and provides high-performance structural materials for the nuclear power field.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118345317B_ABST
    Figure CN118345317B_ABST
Patent Text Reader

Abstract

The present invention relates to a high-strength lead-bismuth corrosion-resistant additively manufactured metastable stainless steel alloy material and a preparation method thereof, comprising the following elements in percentage by mass: C≤0.03wt.%, S≤0.03wt.%, O≤0.1wt.%, N≤0.1wt.%, Cr: 16.0-21.0wt.%, Ni: 10.0-14.0wt.%, Mn: 1.0-2.0wt.%, Mo: 2.0-4.5wt.%, Si: 0.3-1.0wt.%, and the balance is Fe. The alloy powder is prepared by a commercial electrode induction melting gas atomization method, and then the alloy powder is used to obtain an alloy sample by additive manufacturing technology. Compared with the prior art, the metastable stainless steel prepared by the present invention has good room temperature mechanical properties and excellent resistance to liquid lead-bismuth metal corrosion, and can meet the material selection requirements of structural components in lead-bismuth fast reactors.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of additive manufacturing nuclear materials, and in particular relates to an additive manufacturing high-strength metastable steel alloy material resistant to liquid lead-bismuth corrosion and a preparation method thereof. Background Art

[0002] In the process of nuclear energy construction and development, the safety of nuclear reactors is an important prerequisite for ensuring the rapid and healthy development of the industry. Among them, the main source of safety issues in nuclear energy equipment is the harsh service conditions in nuclear reactors. In the fourth-generation lead-bismuth fast reactor, structural materials will serve for a long time in a harsh environment of high temperature (greater than 400°C), high pressure, strong neutron irradiation, and coolant corrosion and scouring. This causes the service performance of the material to deteriorate or even fail. Therefore, the reliability of the materials in the reactor is an important guarantee for the safe and stable operation of the nuclear reactor, and it is also one of the key bottlenecks restricting the development of nuclear energy.

[0003] Stainless steel is currently recognized as a candidate structural material that can be used in liquid lead-bismuth reactors, but the lead-bismuth corrosion problem has always plagued the application of this alloy. On the one hand, the solubility of each component in the alloy in liquid lead-bismuth increases with increasing temperature. On the other hand, the solubility of Ni is much higher than that of Cr and Fe, and the dissolution of Ni in the alloy in liquid lead-bismuth will cause the structure, composition, and surface morphology of the original material to change, and affect many properties of the material. In addition, the surface damage or peeling of the sample caused by dissolution corrosion will remain in the liquid lead-bismuth, and then cause blockage of related flow channels as the coolant circulates. Therefore, the corrosion problem of liquid lead-bismuth alloy on structural steel is a key problem that needs to be solved in the development of lead-bismuth fast reactor structural materials, and is of great significance to the safety and reliability of lead-bismuth fast reactors.

[0004] In order to improve the lead-bismuth corrosion resistance of stainless steel, it is generally achieved by adding alloying elements such as Mo, Ti, Si or adjusting the Cr content in the alloy. eq / Ni eq To improve it, the Mo and Cr contents can be increased and the Ni content can be reduced to give the matrix a dual-phase structure and improve the corrosion resistance of the matrix.

[0005] In addition, the stainless steel produced by traditional casting methods (such as cold rolling and forging) has a large grain size and low material strength. At present, achieving a synergistic improvement in strength and toughness is a hot topic in the field. Due to the rapid melting and solidification process of the powder, the microstructure of the additive manufacturing process is different from that of traditional casting samples. The unique cellular structure, small-angle grain boundaries and dislocations in the matrix make the strength and uniform elongation of the additive samples far exceed those of the same type of products prepared by traditional methods. In addition, additive manufacturing technology has the advantages of short manufacturing cycle and flexible component design, and has been widely used in aerospace, energy and chemical, biomedicine, rail transportation and other fields. In the field of nuclear power, additive manufacturing technology can meet the design requirements of complex structures in nuclear power equipment, so additive manufacturing materials have unlimited application potential in the field of nuclear energy.

[0006] Therefore, in order to reduce production costs while meeting the requirements for the use of steel under severe environmental conditions in lead-bismuth fast reactors and ensuring the integrity of the structural materials used during the life of the reactor, it is necessary to design an additively manufactured metastable stainless steel alloy material that is resistant to lead-bismuth corrosion and has high strength, taking into account the cost, mechanical properties and lead-bismuth corrosion resistance of the alloy. Summary of the invention

[0007] The purpose of the present invention is to overcome the defects of the above-mentioned prior art and to provide a high-strength lead-bismuth corrosion-resistant additively manufactured metastable stainless steel alloy material and a preparation method thereof. By optimizing the alloy composition and printing parameters, the mechanical properties and lead-bismuth corrosion resistance of the metastable stainless steel prepared by additive manufacturing technology are improved, providing design strategies and basic preparation process support for the rapid manufacturing of structural components required in the nuclear power field.

[0008] The purpose of the present invention can be achieved by the following technical scheme: A high-strength lead-bismuth corrosion-resistant additively manufactured metastable stainless steel alloy material, comprising the following elements in percentage by mass: C≤0.03wt.%, S≤0.03wt.%, O≤0.1wt.%, N≤0.1wt.%, Cr: 16.0~21.0wt.%, Ni: 10.0~14.0wt.%, Mn: 1.0~2.0wt.%, Mo: 2.0~4.5wt.%, Si: 0.3~1.0wt.%, and the remainder is Fe.

[0009] Furthermore, the maximum particle size of the alloy powder is less than 150 μm, the hollow ball rate is ≤2%, and the sphericity is ≥95%.

[0010] The present invention also provides a method for preparing a high-strength lead-bismuth corrosion-resistant additively manufactured metastable stainless steel alloy material, comprising the following steps:

[0011] S1: Material preparation: Prepare the following elements according to their mass percentage: C≤0.03wt.%, S≤0.03wt.%, O≤0.1wt.%, N≤0.1wt.%, Cr 16.0~21.0wt.%, Ni 10.0~14.0wt.%, Mn 1.0~2.0wt.%, Mo 2.0~4.5wt.%, Si 0.3~1.0wt.%, and the balance is Fe; Cr in the alloy material is eq / Nieq is greater than 1.95. (where Cr eq is Cr equivalent, satisfying Cr eq =Cr+1.37Mo+1.5Si+2Nb+3Ti (wt.%), Ni eq is Ni equivalent, satisfying Ni eq =Ni+0.31Mn+22C+14.2N+Cu(wt.%)).

[0012] S2: melting the master batches of each element to form an ingot, and obtaining a metastable stainless steel alloy powder by a gas atomization method;

[0013] S3: According to the shape and size of the metal part to be processed, a three-dimensional CAD model of the sample is established using existing three-dimensional modeling software, and the model information is transmitted to the additive manufacturing equipment; the metastable stainless steel alloy powder obtained in step S2 is used as a raw material, and the additive manufacturing equipment is used to print layer by layer to obtain a metastable stainless steel material.

[0014] Furthermore, the melting temperature of step S2 is 1500-1700°C, and the melting vacuum is ≤5×10 -2 Pa.

[0015] Furthermore, the gas atomization method of step S2 is to load the alloy ingot into a leak bag, and the alloy melt flows downward through the leak hole into the gas atomization furnace. Under the action of the inert gas flow, the alloy is crushed into droplets, and finally cooled and solidified into alloy powder.

[0016] Furthermore, the atomization gas pressure is 3-5 MPa, and the inert gas is argon.

[0017] Furthermore, in step S3, the additive manufacturing equipment adopts the strategy of interlayer rotation plus strip scanning, and the process parameters of the additive manufacturing equipment are: laser power 150-250W, scanning speed 750-1250mm / s, layer thickness 0.03-0.05mm, hatch distance 0.08-0.14mm, oxygen content ≤100ppm, laser spot 0.08-0.12mm, substrate preheating 80-120°C. Each layer is rotated 67° between printing, the strip width is 8-12mm, and the strip overlap width is 0.08-0.12mm.

[0018] Furthermore, the tensile strength of the tensile sample of the obtained alloy material perpendicular to the printing direction reaches 680-740MPa at room temperature, the yield strength reaches 650-680MPa, the uniform elongation is 7-13%, and it has good corrosion resistance in a liquid lead-bismuth environment.

[0019] Compared with the prior art, the present invention has the following advantages and beneficial effects:

[0020] 1) Due to the reasonable composition design and the rapid cooling process of additive manufacturing, the metastable steel alloy for additive manufacturing prepared by the present invention realizes a large amount of body-centered cubic (BCC) ferrite phase in the matrix, so that the formed alloy sample has good mechanical properties and lead-bismuth corrosion resistance, effectively solving the problem that steel will suffer from severe corrosion in liquid lead-bismuth, and laying a solid foundation for the preparation of reactor structural parts by additive manufacturing technology;

[0021] 2) The characteristics of the metastable steel alloy powder for additive manufacturing prepared by the present invention meet the characteristic requirements of the additive manufacturing technology for alloy powder, and the preparation process technology has application prospects for the industrial preparation of metastable steel alloy powder; the metastable steel alloy for additive manufacturing of the present invention has good mechanical properties, thus laying an important theoretical and technical foundation for additive manufacturing of high-strength metastable steel materials.

[0022] 3) The metastable steel alloy material and forming process involved in the present invention can solve various technical bottlenecks such as low strength and poor resistance to lead-bismuth corrosion under the commonly used preparation methods of the product, and promote the application of additive manufacturing technology in nuclear power. BRIEF DESCRIPTION OF THE DRAWINGS

[0023] Figure 1 (a) XRD test results and (b) EBSD images of the metastable steel alloy material for additive manufacturing in Example 1 of the present invention.

[0024] Figure 2 This is a microstructure diagram of a metastable steel alloy material for additive manufacturing in Example 1 of the present invention;

[0025] Figure 3 These are cross-sectional morphology photographs of the metastable steel alloy materials for additive manufacturing in (a) Example 1 of the present invention and (b) Comparative Example 3 after being subjected to a 1000 h liquid lead-bismuth corrosion test at 550°C. DETAILED DESCRIPTION

[0026] In order to make the technical solution of the present invention more clear and specific to those skilled in the art, the present invention is described in detail below in conjunction with specific embodiments, but the present invention is not limited to these embodiments.

[0027] Unless otherwise specified, all raw materials and equipment used in the present invention are commercially available products.

[0028] Example 1

[0029] A method for preparing high-strength metastable stainless steel resistant to liquid lead-bismuth corrosion comprises the following steps:

[0030] S1: Material preparation: Prepare raw materials according to the following elements in mass percentage: C≤0.03wt.%, S≤0.01wt.%, O 0.052wt.%, N 0.005wt.%, Cr 19.5wt.%, Ni 10.7wt.%, Mn 1.4wt.%, Mo 2.2wt.%, Si 0.4wt.%, and the balance is Fe.

[0031] S2: Preparation of metastable stainless steel alloy powder: The above raw materials are mixed evenly and added into a smelting furnace for vacuum smelting. The obtained alloy ingots are used for electrode induction melting gas atomization equipment to obtain alloy powder, and then sieved and graded; the gas atomization method is to put the alloy ingot into a leak bag, and the alloy melt enters the gas atomization furnace through the leak hole downward, and then the metastable steel alloy powder is prepared under the atomizing gas pressure with argon as the medium. Among them, the atomizing gas pressure is controlled to be 3-5MPa. The obtained alloy powder is spherical, with a maximum particle size of ≤150μm, a sphericity of ≥95%, and a hollow ball rate of ≤2%.

[0032] S3 uses 3D modeling software (Solidworks software is used in this embodiment) to design a 3D CAD model of the part, and transmits the data information of the STL file to the additive manufacturing molding equipment (EOS GmbH ElectroOptical System EOS M290 model equipment is used in this embodiment). The metastable stainless steel alloy powder obtained in step S2 is spread on the additive manufacturing molding equipment, and the printing process conditions and scanning strategy are set, and the metastable stainless steel alloy material is printed layer by layer. In this embodiment, the interlayer rotation plus strip scanning strategy is adopted, the strip width is 10mm, the strip overlap width is 0.12mm, and the scanning rotation between layers is 67°. The other parameters of the printing process are set as follows: laser power 189W, scanning speed 928mm / s, layer thickness 0.03mm, hatch distance 0.08mm, oxygen content ≤100ppm, laser spot 0.1mm, substrate preheating 80℃.

[0033] The obtained metastable stainless steel alloy material samples were tested for performance: the sample was confirmed to have the presence of BCC phase in XRD test, and the BCC ratio was greater than 80% (e.g. Figure 1). The tensile properties of the metastable steel product were tested perpendicular to the printing direction, and the mechanical properties were as follows: tensile strength 736.52MPa, yield strength 655.52MPa, uniform elongation 12.44%. Static corrosion was carried out in liquid lead-bismuth at 550°C for 1000h, and the maximum corrosion depth was 87.79μm.

[0034] Example 2

[0035] S1: Material preparation: Prepare raw materials according to the following elements in mass percentage: C≤0.03wt.%, S≤0.01wt.%, O 0.04wt.%, N 0.006wt.%, Cr 21.0wt.%, Ni 10.7wt.%, Mn 1.4wt.%, Mo 2.2wt.%, Si0.4wt.%, and the balance is Fe.

[0036] S2: Preparation of metastable stainless steel alloy powder: The above raw materials are mixed evenly and added into a smelting furnace for vacuum smelting. The obtained alloy ingots are used for electrode induction melting gas atomization equipment to obtain alloy powder, and then sieved and graded; the gas atomization method is to load the alloy ingot into a leak bag, and the alloy melt enters the gas atomization furnace through the leak hole downward, and then the metastable steel alloy powder is prepared under the atomizing gas pressure with argon as the medium. Among them, the atomizing gas pressure is controlled to be 3-5MPa. The obtained alloy powder is spherical, with a maximum particle size of ≤150μm, a sphericity of ≥95%, and a hollow ball rate of ≤2%.

[0037] S3 uses 3D modeling software (Solidworks software is used in this embodiment) to design a 3D CAD model of the part, and transmits the data information of the STL file to the additive manufacturing molding equipment (EOS GmbH ElectroOptical System EOS M290 model equipment is used in this embodiment). The metastable stainless steel alloy powder obtained in step S2 is spread on the additive manufacturing molding equipment, and the printing process conditions and scanning strategy are set, and the metastable stainless steel alloy material is printed layer by layer. In this embodiment, the interlayer rotation plus strip scanning strategy is adopted, the strip width is 10mm, the strip overlap width is 0.12mm, and the scanning rotation between layers is 67°. The other parameters of the printing process are set as follows: laser power 189W, scanning speed 928mm / s, layer thickness 0.03mm, hatch distance 0.08mm, oxygen content ≤100ppm, laser spot 0.1mm, substrate preheating 80℃.

[0038] The sample confirmed the presence of BCC phase in XRD detection, and the proportion of BCC in EBSD detection was greater than 80%. The tensile performance test of the metastable steel material product perpendicular to the printing direction was carried out, and the mechanical properties were as follows: tensile strength 734.56MPa, yield strength 649.72MPa, uniform elongation 12.25%. Static corrosion was carried out in liquid lead-bismuth at 550℃ for 1000h, and the maximum corrosion depth was 122.14μm.

[0039] Example 3

[0040] S1: Material preparation: Prepare raw materials according to the following elements in mass percentage: C≤0.03wt.%, S≤0.01wt.%, O 0.05wt.%, N 0.005wt.%, Cr 16.2wt.%, Ni 10.6wt.%, Mn 1.4wt.%, Mo 4.5wt.%, Si0.4wt.%, and the balance is Fe.

[0041] S2: Preparation of metastable stainless steel alloy powder: The above raw materials are vacuum melted, and the obtained alloy ingots are used to obtain alloy powder using electrode induction melting gas atomization equipment, and then screened and graded; the gas atomization method is to load the alloy ingot into a leak bag, and the alloy melt enters the gas atomization furnace through the leak hole downward, and then the metastable steel alloy powder is prepared under the atomizing gas pressure of argon gas as the medium. Among them, the atomizing gas pressure is controlled to be 3-5MPa. The obtained alloy powder is spherical, with a maximum particle size of ≤150μm, a sphericity of ≥95%, and a hollow ball rate of ≤2%.

[0042] S3 uses 3D modeling software (Solidworks software is used in this embodiment) to design a 3D CAD model of the part, and transmits the data information of the STL file to the additive manufacturing molding equipment (EOS GmbH ElectroOptical System EOS M290 model equipment is used in this embodiment). The metastable stainless steel alloy powder obtained in step S2 is spread on the additive manufacturing molding equipment, and the printing process conditions and scanning strategy are set, and the metastable stainless steel alloy material is printed layer by layer. In this embodiment, the interlayer rotation plus strip scanning strategy is adopted, the strip width is 10mm, the strip overlap width is 0.12mm, and the scanning rotation between layers is 67°. The other parameters of the printing process are set as follows: laser power 189W, scanning speed 928mm / s, layer thickness 0.03mm, hatch distance 0.08mm, oxygen content ≤100ppm, laser spot 0.1mm, substrate preheating 80℃.

[0043] The presence of BCC phase was confirmed in the XRD test of the sample. The tensile performance test perpendicular to the printing direction was carried out on the metastable steel material product. The mechanical properties are as follows: tensile strength 735.32MPa, yield strength 649.66MPa, uniform elongation 12.22%. Static corrosion was carried out in liquid lead-bismuth at 550℃ for 1000h, and the maximum corrosion depth was 97.62μm.

[0044] Example 4

[0045] S1: Material preparation: Prepare raw materials according to the following elements in mass percentage: C≤0.03wt.%, S≤0.01wt.%, O 0.06wt.%, N 0.005wt.%, Cr 19.5wt.%, Ni 10.7wt.%, Mn 1.4wt.%, Mo 2.2wt.%, Si0.4wt.%, and the balance is Fe.

[0046] S2: Preparation of metastable stainless steel alloy powder: The above raw materials are vacuum melted, and the obtained alloy ingots are used to obtain alloy powder using electrode induction melting gas atomization equipment, and then screened and graded; the gas atomization method is to load the alloy ingot into a leak bag, and the alloy melt enters the gas atomization furnace through the leak hole downward, and then the metastable steel alloy powder is prepared under the atomizing gas pressure of argon gas as the medium. Among them, the atomizing gas pressure is controlled to be 3-5MPa. The obtained alloy powder is spherical, with a maximum particle size of ≤150μm, a sphericity of ≥95%, and a hollow ball rate of ≤2%.

[0047] S3 uses 3D modeling software (Solidworks software is used in this embodiment) to design a 3D CAD model of the part, and transmits the data information of the STL file to the additive manufacturing molding equipment (EOS GmbH ElectroOptical System EOS M290 model equipment is used in this embodiment). The metastable stainless steel alloy powder obtained in step S2 is spread on the additive manufacturing molding equipment, and the printing process conditions and scanning strategy are set, and the metastable stainless steel alloy material is obtained layer by layer. In this embodiment, an interlayer rotation plus strip scanning strategy is adopted, the strip width is 10mm, the strip overlap width is 0.12mm, and the scanning rotation between layers is 67°. The other parameters of the printing process are set as follows: laser power 214W, scanning speed 928mm / s, layer thickness 0.03mm, hatch distance 0.10mm, oxygen content ≤100ppm, laser spot 0.1mm, substrate preheating 80℃.

[0048] The sample confirmed the presence of BCC phase in XRD detection, and the proportion of BCC in EBSD detection was greater than 80%. The tensile performance test of the metastable steel material product perpendicular to the printing direction was carried out, and the mechanical properties were as follows: tensile strength 737.52MPa, yield strength 665.02MPa, uniform elongation 12.79%. Static corrosion was carried out in liquid lead-bismuth at 550℃ for 1000h, and the maximum corrosion depth was 105.52μm.

[0049] Example 5

[0050] S1: Material preparation: Prepare raw materials according to the following elements in mass percentage: C≤0.03wt.%, S≤0.01wt.%, O 0.06wt.%, N 0.005wt.%, Cr 19.5wt.%, Ni 10.7wt.%, Mn 1.4wt.%, Mo 2.2wt.%, Si0.4wt.%, and the balance is Fe.

[0051] S2: Preparation of metastable stainless steel alloy powder: The above raw materials are vacuum melted, and the obtained alloy ingots are used to obtain alloy powder using electrode induction melting gas atomization equipment, and then screened and graded; the gas atomization method is to load the alloy ingot into a leak bag, and the alloy melt enters the gas atomization furnace through the leak hole downward, and then the metastable steel alloy powder is prepared under the atomizing gas pressure of argon gas as the medium. Among them, the atomizing gas pressure is controlled to be 3-5MPa. The obtained alloy powder is spherical, with a maximum particle size of ≤150μm, a sphericity of ≥95%, and a hollow ball rate of ≤2%.

[0052] S3 uses 3D modeling software (Solidworks software is used in this embodiment) to design a 3D CAD model of the part, and transmits the data information of the STL file to the additive manufacturing molding equipment (EOS GmbH ElectroOptical System EOS M290 model equipment is used in this embodiment). The metastable stainless steel alloy powder obtained in step S2 is spread on the additive manufacturing molding equipment, and the printing process conditions and scanning strategy are set, and the metastable stainless steel alloy material is obtained layer by layer. In this embodiment, an interlayer rotation plus strip scanning strategy is adopted, the strip width is 10mm, the strip overlap width is 0.12mm, and the scanning rotation between layers is 67°. The other parameters of the printing process are set as follows: laser power 189W, scanning speed 750mm / s, layer thickness 0.03mm, hatch distance 0.08mm, oxygen content ≤100ppm, laser spot 0.1mm, substrate preheating 80℃.

[0053] The sample confirmed the presence of BCC phase in XRD detection, and the proportion of BCC in EBSD detection was greater than 80%. The tensile performance test of the metastable steel material product perpendicular to the printing direction was carried out, and the mechanical properties were as follows: tensile strength 737.49MPa, yield strength 651.82MPa, uniform elongation 12.27%. Static corrosion was carried out in liquid lead-bismuth at 550℃ for 1000h, and the maximum corrosion depth was 113.87μm.

[0054] Comparative Example 1

[0055] The preparation method of this comparative example is the same as that of Example 1, except that the added Cr content is 16.5 wt.%.

[0056] No BCC phase was found in the sample in the XRD test, and the steel alloy product was subjected to tensile performance test perpendicular to the printing direction. The mechanical properties are as follows: tensile strength 617.88MPa, yield strength 400.00MPa, uniform elongation 39.73%. Static corrosion was carried out in liquid lead-bismuth at 550°C for 1000h, and the maximum corrosion depth was 193.40μm.

[0057] Comparative Example 2

[0058] The preparation method of this comparative example is the same as that of Example 1, except that the added Cr content is 17.8wt.%.

[0059] No BCC phase was found in the sample in the XRD test, and the steel alloy product was subjected to tensile performance test perpendicular to the printing direction. The mechanical properties are as follows: tensile strength 687.57MPa, yield strength 466.46MPa, uniform elongation 41.81%. Static corrosion was carried out in liquid lead-bismuth at 550°C for 1000h, and the maximum corrosion depth was 225.56μm.

[0060] Comparative Example 3

[0061] The preparation method of this comparative example is the same as that of Example 1, except that the printed sample is subjected to a complete recrystallization treatment at a high temperature of 1300° C. for 6 hours.

[0062] The sample confirmed the presence of BCC phase in XRD detection, and the proportion of BCC in EBSD detection was less than 20%. The metastable steel alloy material product was subjected to tensile performance test perpendicular to the printing direction, and the mechanical properties were as follows: tensile strength 627.44MPa, yield strength 308.77MPa, uniform elongation 42.09%. Static corrosion was carried out in liquid lead-bismuth at 550℃ for 1000h, and the maximum corrosion depth was 270.99μm.

[0063] Comparative Example 4

[0064] The preparation method of this comparative example is the same as that of Example 1, except that the laser power is 300 W, the scanning speed is 1500 mm / s, the layer thickness is 0.03 mm, and the hatch distance is 0.10 mm.

[0065] The metastable steel alloy material product obtained has a large number of unfused holes in the matrix due to insufficient fusion. In the following table, D1 to D3 represent comparative examples 1 to 3 respectively.

[0066] Table 1 Comparison of tensile properties of alloys of the present invention

[0067]

[0068] According to the tensile performance test, the yield strength of the metastable steel in the embodiment of the present invention is greater than 649MPa, the tensile strength is greater than 734MPa, and the uniform elongation is greater than 12%. The yield strength of the metastable steel of the present invention at room temperature is significantly higher than that of the Cr in each comparative example. eq Lower samples (such as Comparative Example 1 and Comparative Example 2).

[0069] Cross-sectional morphology after being corroded in liquid lead-bismuth at 550℃ for 1000h Figure 3 It can be seen that under the same corrosion conditions, the thickness of the corrosion layer in the embodiment of the present invention is less than the thickness of the corrosion layer of the sample in the comparative example, indicating that the metastable steel produced by the additive manufacturing technology of the present invention has good lead-bismuth corrosion resistance. Comparative Example 3 is a sample of the sample of Example 1 after complete recrystallization treatment. The original microstructure of the sample of Comparative Example 3 is similar to the structure of the traditional cast sample, and the matrix is ​​equiaxed crystals with larger grain size, but the BCC content in the alloy prepared by additive manufacturing technology is much higher than this comparative example, indicating that the rapid cooling process in additive manufacturing can change the solidification process of the material, so that there are more BCC phases in the matrix, thereby improving the corrosion resistance of the material.

[0070] Compared with Example 1, Example 2-3 has the same printing process parameters and scanning strategies, but the difference is that different amounts of raw materials are used, and BCC stabilizing elements Cr and Mo are added. It can be seen that although the amounts of raw materials are different, within the scope of the present invention, better mechanical properties and liquid lead-bismuth corrosion resistance can still be obtained.

[0071] Compared with Example 1, Examples 4-5 have the same amount of raw materials and different printing process parameters, but within the scope of the present invention, good mechanical properties and liquid lead-bismuth corrosion resistance can still be obtained. However, due to the excessively fast scanning speed, the energy density of the input molten pool in Comparative Example 4 is too low, resulting in incomplete fusion defects.

[0072] The above specific embodiments of the present invention are for the convenience of ordinary technicians in the technical field to understand and use the invention. It should be noted that the present invention is not limited to the above specific implementations, and those familiar with the technical field can make various changes or modifications within the scope of the claims, which does not affect the essential content of the present invention. Therefore, the present invention is not limited to the above embodiments, and improvements and modifications made by those skilled in the art based on the disclosure of the present invention without departing from the scope of the present invention should be within the scope of protection of the present invention.

Claims

1. A high-strength lead-bismuth corrosion-resistant additively manufactured metastable stainless steel alloy material, characterized in that: The following elements are included in percentage by weight: C≤0.03 wt.%, S≤0.03 wt.%, O≤0.1 wt.%, N≤0.006 wt.%, Cr: 16.0~21.0 wt.%, Ni: 10.0~14.0 wt.%, Mn: 1.0~2.0 wt.%, Mo: 2.0~4.5 wt.%, Si: 0.3~1.0 wt.%, and the balance is Fe; and Cr eq is Cr equivalent, satisfying Cr eq = Cr + 1.37 Mo + 1.5Si + 2Nb + 3Ti (wt.%), Ni eq is Ni equivalent, satisfying Ni eq = Ni + 0.31Mn + 22C + 14.2N + Cu (wt.%), Cr in the alloy material eq / Ni eq Greater than 1.95; the alloy material is prepared by the following method: S1: Material preparation: Prepare the materials according to the following mass percentage of elements: C≤0.03 wt.%, S≤0.03 wt.%, O≤0.1wt.%, N≤0.006 wt.%, Cr 16.0~21.0 wt.%, Ni 10.0~14.0 wt.%, Mn 1.0~2.0 wt.%, Mo 2.0~4.5 wt.%, Si 0.3~1.0 wt.%, and the balance is Fe; S2: Each element masterbatch is melted to form an ingot, and a metastable stainless steel alloy powder is obtained by a gas atomization method; specifically, the alloy ingot is loaded into a leak bag, and the alloy melt passes downward through the leak hole into a gas atomization furnace, and under the action of an inert gas argon gas flow, the alloy is crushed into droplets, and finally cooled and solidified into alloy powder; S3: According to the shape and size of the metal parts to be processed, a three-dimensional CAD model of the sample is established by using the existing three-dimensional modeling software, and the model information is transmitted to the additive manufacturing equipment; the metastable stainless steel alloy powder obtained in step S2 is used as a raw material, and the additive manufacturing equipment is used to print layer by layer to obtain a metastable stainless steel material. The process parameters of the additive manufacturing equipment are: laser power 150-250 W, scanning speed 750-1250 mm / s, layer thickness 0.03-0.05 mm, hatch distance 0.08-0.14 mm, oxygen content ≤100 ppm, laser spot 0.08-0.12 mm, substrate preheating 80-120 °C.

2. The high-strength lead-bismuth corrosion-resistant additively manufactured metastable stainless steel alloy material according to claim 1 is characterized in that: The maximum particle size of the alloy powder is less than 150 μm, the hollow ball rate is ≤2%, and the sphericity is ≥95%.

3. A method for preparing a high-strength lead-bismuth corrosion-resistant additively manufactured metastable stainless steel alloy material as claimed in any one of claims 1 to 2, characterized in that: The following steps are involved: S1: Material preparation: Prepare the materials according to the following mass percentage of elements: C≤0.03 wt.%, S≤0.03 wt.%, O≤0.1wt.%, N≤0.1 wt.%, Cr 16.0~21.0 wt.%, Ni 10.0~14.0 wt.%, Mn 1.0~2.0 wt.%, Mo 2.0~4.5 wt.%, Si 0.3~1.0 wt.%, and the balance is Fe; S2: melting the master batches of each element to form an ingot, and obtaining a metastable stainless steel alloy powder by a gas atomization method; S3: According to the shape and size of the metal part to be processed, a three-dimensional CAD model of the sample is established using existing three-dimensional modeling software, and the model information is transmitted to the additive manufacturing equipment; the metastable stainless steel alloy powder obtained in step S2 is used as a raw material, and the additive manufacturing equipment is used to print layer by layer to obtain a metastable stainless steel material.

4. The method for preparing a high-strength lead-bismuth corrosion-resistant additively manufactured metastable stainless steel alloy material according to claim 3, characterized in that: The melting temperature of step S2 is 1500-1700°C, and the melting vacuum is ≤5×10 -2 Pa.

5. The method for preparing a high-strength lead-bismuth corrosion-resistant additively manufactured metastable stainless steel alloy material according to claim 3, characterized in that: The atomization air pressure is 3-5 MPa.

6. The method for preparing a high-strength lead-bismuth corrosion-resistant additively manufactured metastable stainless steel alloy material according to claim 3, characterized in that: In step S3, the additive manufacturing equipment adopts an inter-layer rotation plus strip scanning strategy, with a 67° rotation between each layer printing, a strip width of 8-12 mm, and a strip overlap width of 0.08-0.12 mm.

7. The method for preparing a high-strength lead-bismuth corrosion-resistant additively manufactured metastable stainless steel alloy material according to claim 3, characterized in that: The tensile strength of the tensile sample of the obtained alloy material perpendicular to the printing direction reaches 680-740 MPa at room temperature, the yield strength reaches 650-680 MPa, the uniform elongation is 7-13%, and it has good corrosion resistance in liquid lead-bismuth environment.

Citation Information

Patent Citations

  • Manufacturing process of high-strength corrosion-resistant additive manufacturing stainless steel

    CN113263174A

  • High-corrosion-resistance stainless steel additive manufacturing process

    CN115026307A